Adolescents' Intake of Junk Food: Processes and Mechanisms Driving Consumption Similarities Among Friends. (19th August 2013) - de la, Kayla; Robins, Garry; Mohr, Philip; Wilson, Carlene
<x xml:space="preserve">Abstract</x> Adolescents' consumption of low‐nutrient, energy‐dense (LNED) food often occurs out of home, and friends may be an important source of influence. This study tested whether observed similarities in LNED food intake among friends result from social influence and also explored underlying psychological mechanisms. Three waves of data were collected over 1 year from Grade 8 students in Australia (N = 378, 54% male), including measures of food intake and related cognitions, and friendships to grademates. The results of longitudinal social network models show that adolescent intake was predicted by their friends' intake, accounting for pre‐existing similarities and other potentially confounding factors. Changes to adolescents' beliefs about LNED food do not appear to be the mechanisms underpinning influence from their friends.